ANALISIS DATA GOVERNANCE MATURITY MENGGUNAKAN STANDFORD DATA GOVERNANCE MATURITY - Yulfitri, Alivia (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2020)
Data services are the core business of the services of Institution A. Providing reliable data quality is the company's top priority. Data governance is important in striving for good data quality so that data is not duplicated, accurate, valid, and can be accessed at any time. At present, there is no official data governance at institution A. For this reason, an analysis data governance maturity in institution A. An assessment and analysis of the components of formalization, awareness and management, which includes the dimensions of people, policies and technology. This activity aims to determine the level of maturity of data governance, conduct gap analysis, and provide recommendations on data governance initiatives. The method used is to assess the maturity level of data governance, designing questionnaires, distributing questionnaires, and in-depth interviews. The standard referred to is the Standford Data Governance maturity, which is then adjusted to the conditions of the organization. The results of this study are the analysis of the maturity of data governance and recommendations for data governance initiatives to achieve expected conditions.